Analysis of the relationship between learning styles and student learning outcomes in the digital era - Tedi Gandara; Imas Masitoh; Rista Erika; Mia Siti Nurazizah (At Turots: Jurnal Pendidikan Islam, 2025)
The accelerating integration of digital technologies in education has transformed how learners engage with content, making learning styles—visual, auditory, and kinesthetic—potentially significant in shaping academic performance. Drawing upon recent empirical evidenceThis study seeks to explore the correlation between learning styles and student learning outcomes. within digital learning environments. Employing a quantitative correlational design with secondary school students, data will be collected via standardized learning style inventories and academic performance metrics. Analytical methods include Pearson correlation and regression analysis. Findings are anticipated to offer new empirical insights into how personal learning preferences interact with digital modalities and will have practical implications for educators and policymakers in designing inclusive, technology-enhanced pedagogy.